Biopedagogía en Enfermería y Enfermería biopedagógica. - Ana Leticia Rodríguez Araya (Universidad de Costa Rica, 2011)
This essay proposes and rediscovers the passionate interrelation between nursing and biopedagogy. It makes the permanent presence of learning from life evident in nursing as an art from its historical roots. From the ontological femininity that gave it meaning, nursing represents itself as rhythmic and sequentially interwoven to biopedagogy, and both, as units, integrated to a whole which constitutes a quantum leap5 which in turn transforms complexity into simplicity and vice versa; therefore, creativity becomes complex. The sources that nurture and keep the intricacies of nursing and biopedagogy proposed here emerge from the powerful kotodama6 of Florence Nightingale, insigne modern nursing founder.